Affibody-Mediated Sequestration of Amyloid β Demonstrates Preventive Efficacy in a Transgenic Alzheimer’s Disease Mouse Model - Boutajangout, Allal; Lindberg, Hanna; Awwad, Abdulaziz; Paul, Arun; Baitalmal, Rabaa; Almokyad, Ismail; Höidén-Guthenberg, Ingmarie; Gunneriusson, Elin; Frejd, Fredrik Y.; Härd, Torleif; Löfblom, John; Ståhl, Stefan; et al. (Frontiers in Aging Neuroscience, 2019)
Different strategies for treatment and prevention of Alzheimer’s disease (AD) are currently under investigation, including passive immunization with anti-amyloid beta (Aβ) monoclonal antibodies (mAbs). Here, we investigate the therapeutic potential of a novel type of Aβ-targeting agent based on an affibody molecule with fundamentally different properties to mAbs. We generated a therapeutic candidate, denoted ZSYM73-ABD (16.8 kDa), by genetic linkage of the dimeric ZSYM73 affibody for sequestering of monomeric Aβ-peptides and an albumin-binding domain (ABD) for extension of its in vivo half-life. APP/PS1 transgenic AD mice were administered with ZSYM73-ABD, followed by behavioral examination and immunohistochemistry. Results demonstrated rescued cognitive functions and significantly lower amyloid burden in the treated animals compared to controls. No toxicological symptoms or immunology-related side-effects were observed. To our knowledge, this is the first reported in vivo investigation of a systemically delivered scaffold protein against monomeric Aβ, demonstrating a therapeutic potential for prevention of AD.